Fabrication of multifunctional alginate microspheres containing hydroxyapatite powder for simultaneous cell and drug delivery - Kim, Jueun; Choi, Yeong-Jin; Park, Honghyun; Yun, Hui-suk (Frontiers in Bioengineering and Biotechnology, 2022)
Novel alginate-hydroxyapatite hybrid microspheres were developed for simultaneous delivery of drugs and cells as a multifunctional bone substitute for osteoporotic bone tissue regeneration. The microspheres were used to enhance osteogenesis and to carry and deliver quercetin, a representative phytoestrogen that controls bone tissue regeneration metabolism in osteoporosis patients, through sustained release over a long period. To overcome quercetin’s hydrophobicity and low solubility in aqueous environments, we added it to the surface of hydroxyapatite (HAp) nanoparticles before mixing them with an alginate solution. The homogeneous distribution of the HAp nanoparticles in the alginate solution was essential for preventing nozzle clogging and achieving successfully fabricated hybrid microspheres. To this end, a 3D ultrasonic treatment was applied. Electrostatic microencapsulation was then used to fabricate hybrid alginate-HAp microspheres containing quercetin and cells. The microspheres were approximately 290.7 ± 42.5 μm (aspect ratio of 1). The sustained release of quercetin was confirmed during a test period of 20 weeks. The cells in the hybrid microspheres maintained good cell viability during the entire testing period, and their osteogenic differentiation behavior was boosted by the presence of HAp. Thus, osteogenic differentiation could be greatly improved by adding quercetin. These novel multi-biofunctional hybrid microspheres have great potential for the regeneration of osteoporotic bone tissue at indeterminate defect sites.